An Analysis the Cultural Patterns on Students Group Learning in EFL Classroom - Sujariati Sujariati (Universitas Muhammadiyah Mataram, 2020)
The objectives of this research were to found out the cultural patterns used by the students and investigated the influences of cultural pattern on student’s group learning and their communication. This research applied qualitative method. This research employed observation and interview. The subject research were 50 female students in Gombara boarding school Makassar. The findings showed that the students’ interaction in learning was indicated in various cultures and attributes as they interacted in their groups. Cultural patterns were found such as beliefs, positive and negative values, and norms. Cultural beliefs indicated when students contributed to each person’s unique configuration and expectations within the larger cultural matrix. Some students applied positive values like practiced and appreciated their culture and customs in the way they interacted in learning and communication attributed a few self-centered in their social attitude from a selfish attitude to be more active in sharing ideas in communication and learning. It was also found negative values such as member of individualistic cultures or collectivistic orientation students on group communication or group learning. Some students demonstrated sharing attitude but they did not practice them throughout their group work, they were more individualistic and preferred individual work. Dealt with norms, some students indicated to guide people’s interaction and to engage in conversation through a good manner.